Pertimbangan Maṣlaḥah dalam Penetapan Dispensasi Kawin: Analisis Penetapan PA Purworejo No.113/PDT.P/2025/PA/PWR - Praptining Hayu Trisnasih; Waluyo Sudarmaji; Arifuat Marzuki (AL-SULTHANIYAH, 2026)
The granting of marriage dispensations by the Religious Court is a legal exception to the minimum age limit for marriage as stipulated in Law Number 16 of 2019. This condition raises legal issues, particularly regarding the judge's consideration in assessing the benefits and potential harm of early marriage. This study aims to analyze the consideration of maṣlaḥah in granting marriage dispensations and the factors underlying the judge's assessment of the existence of urgent maṣlaḥah in Religious Court Decision Number 113/Pdt.P/2025/PA/Pwr. This study is a normative legal study with a judicial decision study approach. The research data consists of primary data in the form of court decisions and secondary data in the form of laws and regulations, Islamic legal literature, and relevant academic studies. The results of the study show that judges grant marriage dispensation requests based on considerations of maṣlaḥah ḍarūriyyah, particularly in preserving lineage (ḥifẓ al-nasl) and rejecting greater mafsadah. The main factors underlying the approval are the existence of an out-of-wedlock pregnancy, the physical, mental, and economic readiness of both prospective spouses, family support, and the application of the fiqh principle of dar'ul mafasid muqaddamun 'ala jalbil masalih. This decision indicates that marriage dispensation is viewed as a legal protection instrument in the best interests of the child.